2000
DOI: 10.1128/iai.68.6.3172-3179.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Binding of Candida albicans to Small Intestinal Mucin and Its Role in Adherence to Mucosal Epithelial Cells

Abstract: In order to approximate and adhere to mucosal epithelial cells, Candida must traverse the overlying mucus layer. Interactions of Candida species with mucin and human buccal epithelial cells (BECs) were thus investigated in vitro. Binding of the Candida species to purified small intestinal mucin showed a close correlation with their hierarchy of virulence. Significant differences (P < 0.05) were found among three categories of Candida species adhering highly (C. dubliniensis, C. tropicalis, and C. albicans), mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
0
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 64 publications
2
64
0
6
Order By: Relevance
“…Moreover, it was demonstrated that the degraded mucins were less effective in inhibiting adherence of amoebae to target epithelial cells, indicating that the mucin polymer must be intact to maintain its protective function. Similar observations have been reported for Candida albicans, where the mucin was degraded by the secreted aspartyl protease Sap2p (14). E.h. trophozoites expressing the antisense message to EhCP5 (E.h. cysteine protease 5) (15) have an impaired ability to disrupt an intact colonic mucus barrier and invade epithelial cell monolayers (16).…”
supporting
confidence: 73%
“…Moreover, it was demonstrated that the degraded mucins were less effective in inhibiting adherence of amoebae to target epithelial cells, indicating that the mucin polymer must be intact to maintain its protective function. Similar observations have been reported for Candida albicans, where the mucin was degraded by the secreted aspartyl protease Sap2p (14). E.h. trophozoites expressing the antisense message to EhCP5 (E.h. cysteine protease 5) (15) have an impaired ability to disrupt an intact colonic mucus barrier and invade epithelial cell monolayers (16).…”
supporting
confidence: 73%
“…2. Sap2 is known to degrade many human proteins including molecules that protect mucosal surfaces such as mucin (36,52) and secretory immunoglobulin A (IgA) (78,184). Not only could this provide essential nitrogen for growth, but also it could enhance attachment, colonization, and penetration of host tissue by the removal of host barriers.…”
Section: Degradation Of Human Proteins and Structural Analysis Inmentioning
confidence: 99%
“…Examples of such characteristics include the inability to grow at 45°C, the production of multiple terminal chlamydoconidia, and assimilation of xylose. C. dubliniensis appears to have greater expression than C. albicans of some characteristics generally considered to be associated with virulence, such as aspartyl protease production and possibly adhesion to buccal epithelial cells (7,8,12,44), although its ability to bind to mucin appears similar to that of C. albicans (9). C. dubliniensis also appears to more easily develop resistance to fluconazole, which is commonly used to treat oropharyngeal candidiasis (6,56,57).…”
mentioning
confidence: 99%